The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.heliyon.2020.e04951
|View full text |Cite
|
Sign up to set email alerts
|

Direct suppression of human islet dedifferentiation, progenitor genes, but not epithelial to mesenchymal transition by liraglutide

Abstract: β-cell dedifferentiation has been accounted as one of the major mechanisms for β-cell failure; thus, is a cause to diabetes. We study direct impacts of liraglutide treatment on ex vivo human dedifferentiated islets, and its effects on genes important in endocrine function, progenitor states, and epithelial mesenchymal transition (EMT). Human islets from non-diabetic donors, were purified and incubated until day 1 and day 4, and were determined insulin contents, numbers of insulin (INS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…In pancreatic islet cultures from non-diabetic patients, β-cell dedifferentiation progresses over time, and their insulin content decreases by 50% in about one week. When this happens, the expression of mature β-cell markers (Pdx-1 and MafA) is decreased, and the expression of endocrine progenitor cell markers (Ngn3 and Aldh1a) is increased [ 48 ]. The addition of GLP-1 to human islets suppressed the expression of these dedifferentiation markers, and knockdown of FoxO1 diminished these effects, suggesting that FoxO1 may be involved in the GLP-1-induced suppression of pancreatic β-cell dedifferentiation [ 48 ].…”
Section: Pancreatic β-Cell Dedifferentiation and Transdifferentiationmentioning
confidence: 99%
“…In pancreatic islet cultures from non-diabetic patients, β-cell dedifferentiation progresses over time, and their insulin content decreases by 50% in about one week. When this happens, the expression of mature β-cell markers (Pdx-1 and MafA) is decreased, and the expression of endocrine progenitor cell markers (Ngn3 and Aldh1a) is increased [ 48 ]. The addition of GLP-1 to human islets suppressed the expression of these dedifferentiation markers, and knockdown of FoxO1 diminished these effects, suggesting that FoxO1 may be involved in the GLP-1-induced suppression of pancreatic β-cell dedifferentiation [ 48 ].…”
Section: Pancreatic β-Cell Dedifferentiation and Transdifferentiationmentioning
confidence: 99%
“…Nevertheless, among the intrinsic factors, the observed decrease in other islet hormones and neuroendocrine marker CHGA abundance advances a scenario in which the decreased insulin abundance in the islets of the LOW insulin group is part of a more general phenomenon of dedifferentiation. During dedifferentiation, islet cells reduce or even lose the expression of key markers 32,33 leading to their metabolic reconfiguration and ultimately, | 11 of 15 MATHISEN et al in the case of beta-cells, defective insulin secretion. 34 In our pilot study, we identified both the loss of key markers and changes affecting metabolic signature of the islets, including the inhibition of insulin secretion pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Islet cell dedifferentiation is a known pathological phenomenon in the development of diabetes, in mice 35,36 as well as in humans, especially in the context of T2D. [37][38][39] Moreover, it is known to affect islets in culture 33,40 in a time-dependent fashion. As all islet samples analyzed were cultured for the same amount of time, the observed dedifferentiation event must have a different trigger.…”
Section: Discussionmentioning
confidence: 99%